Effectiveness of Personal Protective Equipment (PPE) at Construction Site - Mohd Amir Shazwan, Hashim; Ee, Jiah May (INTI International University, 2018)
It is axiomatic that, most cases in regards to the accidents around the vicinity of construction site has always been happening in Malaysia. In fact, we had collected and accumulated the data through questionnaires surveys with the Grade 7 contractors. In which, they are all with licence and registered under Construction Industry Development Berhad (CIDB) at Petaling Distinct. Seemingly, accidents tends to happen at the construction site due to the cause of improper usage of personal proper equipment (PPE) and the stubbornness in refusing to wear the personal proper equipment (PPE). Notably, this research is served to raise an awareness to the workers and employees respectively, in order to encourage them for using the appropriate equipment in proper. Certainly, there are several ways to strategize on giving an encouragement and awareness among the workers and employees, that includes (i) Providing them a proper training of using the equipment, (ii) Select the suitable PPE based on the relevant tasks given and (iii) Maintenance of the PPE. Ultimately, the risk of fatal accidents that happens at the construction sites will diminished and reduced by way of the usage of PPE. Indeed, the effectiveness of PPE may seems to be convinced, however, that could depends on the experiences, capability, knowledge with skills, attitude and belief of the workers and employees in regards to the use of PPE at construction sites. Solely, by way of prevention and deterrence, it will reduce the amount of construction site accidents and ultimately broaden their horizons on the usage of PPE. Doubtlessly, this research can be used as a reference source in the site for safety precaution.